Crisis of Faith: Today's African Christians and Mami-Wata (Mother-Water) Spirituality - Uzukwu, Gesila Nneka (Journal of ecumenical studies, 2024)
, precis:, This study provides an analysis of the impact of Mami-Wata spirituality on an understanding of the place and fate of Christianity in Africa today. A section of the Christian population negotiates their Christian beliefs through the prism of their traditional African religious cosmology and worldviews. This new Christian African spirituality is generating waves of faith crises. While previous scholarship has investigated the crises of African Christian faith from the dominant point of view of African culture and context, from Christian-Muslim interaction, or from the influence of Western elements, there are no works that show the multidimensional impacts of Mami-Wata spirituality on Christians and their faith, identity, and theological discourses. Departing from past works, the present work investigates how rudimentary constructs of African spirituality have engaged Christianity on several fronts, from the problem of faith crisis and the engagement of the Mami-Wata deity to how some African Christians wrestle with their devotion to the Virgin Mary vis-à-vis the traditional Mami-Wata deity. This analysis also demonstrates the indispensability of the female divine in spiritual and religious discourses, and it provides a pathway to construct a theology that is both truly Christian and grounded in African realities.